REVIEW: INOVASI ZAT AKTIF DALAM FORMULASI GRANUL EFFERVESCENT DARI EKSTRAK HERBAL - Fatimah Salsabila Algina; Oktriyisa Tantia Mini; Surya Alvina Nazaha; Zulfa Muthi’ah; Mirnawati, Mirnawati; Nor Latifah (Jurnal Cakrawala Ilmiah, 2024)
This study aims to explore the innovative incorporation of active compounds from herbal extracts into effervescent granule formulations. Effervescent granules, known for their rapid dissolution and pleasant taste, have gained significant interest in the pharmaceutical industry. The utilization of herbal extracts as active ingredients in these formulations offers a promising approach to develop novel and natural-based pharmaceutical products. This review will delve into various aspects, including the selection of appropriate herbal extracts, the formulation process, and the evaluation of the physicochemical properties of the resulting granules. Additionally, the challenges and opportunities associated with the development of herbal-based effervescent granules will be discussed. By providing a comprehensive overview of the current state-of-the-art, this review seeks to stimulate further research and development in this exiciting area of pharmaceutical sciences.